Pergeseran Orientasi dan Ekspresi Elit Pesantren di Kota Tasikmalaya - Satori, Akhmad; Nurohman, Taufik (JSW (Jurnal Sosiologi Walisongo), 2018)
This study focuses on the changing of orientation and expression among the elites of pesantren in Tasikmalaya in the effort to form a community life that is in accordance with the culture and values of Islamic teachings. To answer the questions, a descriptive-qualitative research method with a phenomenological approach is used in this study. The results of the study show that there are differences in views related to religious relations with the state, especially those which related to the intersection of Islamic Law with the legal system that applies among pesantren in Tasikmalaya. The first view states that to find solutions to various problems of society and in forming an Islamic society requires the involvement of the State; The second view states that to form an Islamic society does not need to involve the state. This view is more supportive of the implementation of religious ethics or morals with a cultural approach. The third view is the view which is a compromise between the two groups in the making of regulations.